Kinetics and equilibrium adsorption study of selenium oxyanions onto Al/Si and Fe/Si coprecipitates. (May 2018) - Chan, Y.T.; Liu, Y.T.; Tzou, Y.M.; Kuan, W.H.; Chang, R.R.; Wang, M.K.
Abstract: Inappropriate treatments for the effluents from semiconductor plants might cause the releases and wide distributions of selenium (Se) into the ecosystems. In this study, Al/Si and Fe/Si coprecipitates were selected as model adsorbents as they often formed during the wastewater coagulation process, and the removal efficiency of selenite (SeO3 ) and selenate (SeO4 ) onto the coprecipitates were systematically examined. The removal efficiency of SeO3 and SeO4 was highly related to surface properties of Al/Si and Fe/Si coprecipitates. The surface-attached Al shell of Al/Si coprecipitates shielded a portion of negative charges from the core SiO2, resulting in a higher point of zero charge than that of Fe/Si coprecipitates. Thus, adsorption of SeO3 /SeO4 was favorable on the Al/Si coprecipitates. Adsorptions of both SeO3 and SeO4 on Al/Si coprecipitates were exothermic reactions. On Fe/Si coprecipitates, while SeO3 adsorption also showed the exothermic behavior, SeO4 adsorption occurred as an endothermic reaction. The kinetic adsorption data of SeO3 /SeO4 on Al/Si and Fe/Si coprecipitates were described well by the pseudo-second-order kinetic model. SeO4 and SeO3 adsorption on Fe/Si or Al/Si were greatly inhibited by the strong PO4 ligand, whereas the weak ligand such as SO4 only significantly affected SeO4 adsorption. The weakest complex between SeO4 and Al was implied by the essentially SeO4 desorption as SeO4 /PO4 molar ratios decreased from 0.5 to 0.2. These results were further confirmed by the less SeO4 desorption (41%) from Fe/Si coprecipitates than that from Al/Si coprecipitates (78%) while PO4 was added sequentially. Graphical abstract: Highlights: Adsorptions of Se oxyanions on Al/Si coprecipitates were exothermic processes. SeO3 adsorption on Fe/Si coprecipitates was an endothermic reaction. PO4 addition reduced up to 83–89% of SeO3 /SeO4 adsorption from Al/Si coprecipitates. PO4 addition reduced up to 75–77% of SeO3 /SeO4 adsorption from Fe/Si coprecipitates. Se adsorptions were controlled by structural and surface properties of coprecipitates.